SLEEP DISORDERS IN CHILDREN WITH DISEASES OF THE NERVOUS SYSTEM, ENT PATHOLOGY AND ALLERGY - E. A. Abashidze (Union of pediatricians of Russia, 2012)
The purpose of this study was to assess the nature of the sleep changes in children with various pathologies. The study included 103 children with diseases of the nervous system, ENT disorders and allergic diseases. Polysomnography was carried out to all children - the synchronous recording of various physiological parameters during sleep. The vast majority of patients in the studied groups had changed microstructure of sleep in comparison with the healthy children (control group). Disorders of breathing during sleep were manifested in the form of episodes of apnea/hypopnea. These changes were associated with the severity of somatic pathology.